26. Effectiveness in indirect decompression using mis tlif in single level lumbo-sacral spondylolisthesis - Kien, Tran Trung; Hung, Kieu Dinh; Ha, Duong Dai; Tan, Hoang Minh; Trung, Tran Quang (Tạp chí Nghiên cứu Y học, 2024)
Minimally invasive surgery - transforaminal lumbar interbody fusion (MIS TLIF) was considered as a promising treatment in lumbo-sacral spondylolisthesis, especially using intraoperative neuromonitoring will provide safer and faster recovery with less complications. The objective of this study was to confirmed the safety of the innovative MIS TLIF in releasing nerves without exposure. From 2022 to March 2024, 20 single-level lumbo-sacral spondylolisthesis was performed for indirect decompression using MIS TLIF with intraoperation neuromonitoring. During perioperative and follow-up, demographic data, operation time, blood loss, VAS, ODI, modified MacNab criteria, radiographic evaluation and complications were collected and analyzed. 20 patients were followed up for more than 12 months. Mean age: 52.1 and mean follow-up 15.2 months. VAS back pain: 7.4 preoperatively and 0.8 at the final. VAS of leg pain was 7.1 preoperatively and 0.9 at the final. ODI was 52.4% preoperatively and 15.6% at the final. MIS-TLIF was associated with reduction of spondylolisthesis, increase in disc height (+6 mm), foraminal height (+3,1 mm), and segmental lordosis (+4.8°). Patients with hypolordosis (<40°) significant increases +6.1° and overall lordosis +7.6°. Pelvic parameters were not significantly changed. According to the modified MacNab criteria: 75% excellent, 20% good and 51% fair. There was no complication perioperatively. Indirect decompression using MIS TLIF seems to be a safe, effective, and feasible technique in managing single level lumbo-sacral spondylolisthesis.